Endothelial Glycocalyx Integrity in Treatment-Naïve People Living with HIV before and One Year after Antiretroviral Treatment Initiation - Paraskevi C. Fragkou; Ignatios Ikonomidis; Dimitrios Benas; Dimitra Kavatha; Charalampos D. Moschopoulos; Konstantinos Protopapas; Gavriella Kostelli; John Thymis; Dionysia Mpirmpa; Irene Galani; Maria Tsakona; Chrysanthi Oikonomopoulou; et al. (Viruses, 2023)
Endothelial glycocalyx (EG) derangement has been associated with cardiovascular disease (CVD). Studies on EG integrity among people living with HIV (PLWH), are lacking. We conducted a prospective cohort study among treatment-naïve PLWH who received emtricitabine/tenofovir alafenamide, combined with either an integrase strand transfer inhibitor (INSTI, dolutegravir, raltegravir or elvitegravir/cobicistat), or a protease inhibitor (PI, darunavir/cobicistat). We assessed EG at baseline, 24 (±4) and 48 (±4) weeks, by measuring the perfused boundary region (PBR, inversely proportional to EG thickness), in sublingual microvessels. In total, 66 consecutive PLWH (60 (90.9%) males) with a median age (interquartile range, IQR) of 37 (12) years, were enrolled. In total, 40(60.6%) received INSTI-based regimens. The mean (standard deviation) PBR decreased significantly from 2.17 (0.29) μm at baseline to 2.04 (0.26) μm (p = 0.019), and then to 1.93 (0.3) μm (p < 0.0001) at 24 (±4) and 48 (±4) weeks, respectively. PBR did not differ among treatment groups. PLWH on INSTIs had a significant PBR reduction at 48 (±4) weeks. Smokers and PLWH with low levels of viremia experienced the greatest PBR reduction. This study is the first to report the benefit of antiretroviral treatment on EG improvement in treatment-naïve PLWH and depicts a potential bedside biomarker and therapeutic target for CVD in PLWH.